KUALITAS PELAYANAN TICKETING PADA PT. SYAM TOUR AND TRAVEL PEKANBARU - Nindia Claudia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research in this thesis is a descriptive quantitative research, the author describes matters relating to the quality of service ticketing in PT. Syam Tour and Travel Pekanbaru. Data collection methods used in this study was a questionnaire in the form of written questions given to respondents that aims to determine the quality of service ticketing in PT. Syam Tour and Travel Pekanbaru and to know the efforts in improving the quality of service ticketing in PT. Syam Tour and Travel Pekanbaru. Known to the acquisition of the total score of each variable ticketing service quality research at PT. Sham Tour and Travel Pekanbaru as follows : Tangibles with a total score of 865 points, a total Empathy with a total score of 800 points, Reliability with a total score of 782 points, Responsiveness with a total score of 1,200 points, Assurance with a total score of 859 points. Thus the quality of service ticketing in PT. Syam Tour and Travel Pekanbaru considered still need improvement to the quality of ticketing services to customers of PT. Syam Tour and Travel Pekanbaru. Known quality of service ticketing in PT. Syam Tour and Travel Pekanbaru pretty good and less good. It is known from the acquisition of each of the variables that the authors describe in a research questionnaire that was distributed to the respondents / customers in PT. Syam Tour and Travel Pekanbaru.Keywords : Reliability, Responsiveness, Assurance, Tangible, Empathy